Straw return regimes improve mollisol quality by reshaping microbial composition and metabolic profiles - Xinyuan Li; Yanhui Dou; Tingting Cui; Jing Xu; Yuxian Wang; Junqiang Wang; Rong Jiang; Shumin Sun; Guanghui Hu; Wanrong Gu (Applied Soil Ecology, 2026)

Infant-derived bifidobacterium can enhance the ability to respond to influenza virus infection by promoting type I interferon-mediated immunity - Jiaqian Shentu; Qinggang Xie; Minghui Yan; Shumin Wang; Xiaoxuan Sun; Chengcheng Zhang; Peijun Tian; Xiaomei Lv; Bo Yang; Wenwei Lu; Shumao Cui; Gang Wang; et al. (Food Bioscience, 2026)

Revising the coal mining CH4 emission factor based on multiple inventories and atmospheric inversion approach at one of the world's largest coal production areas: Shanxi province, China - Xuejing Shi; Yiyi Peng; Shumin Wang; Yifan Zhang; Junqing Zhang; Hao Song; Yu Cui; Fan Sun; Huili Liu; Qitao Xiao; Ning Hu; Wei Xiao; et al. (Science of The Total Environment, 2025)

Early life gut microbiota: Consequences for health and opportunities for prevention - Shumin Wang; Jingjing Cui; Shilong Jiang; Chengdong Zheng; Jianxin Zhao; Heng Zhang; Qixiao Zhai (Critical Reviews in Food Science and Nutrition, 2024)

Occurrence and distribution of antibiotic pollution and antibiotic resistance genes in seagrass meadow sediments based on metagenomics - Kaixuan Cui; Shumin Wang; Yanzhao Pei; Bin Zhou (Science of The Total Environment, 2024)

The effect of L-cysteine on starch and protein degradation during barley germination - Shumin Hu; Qingqing Qin; Cui Zhang; Junhong Yu; Shuli Huang; Jia Liu; Zhaoxia Yang (Biotechnology Letters, 2024)

Synchronized achieving amount reduction and efficiency increase of lithium salt-type additive by alternating current pulse discharge technology - Shiyou Li; Yulong Zhang; Shumin Wu; Yin Quan; Meiling Wu; Peng Wang; Dongni Zhao; Xiaoling Cui (Chemical Engineering Journal, 2024)

Zinc Oxide Nanoparticles Trigger Autophagy in the Human Multiple Myeloma Cell Line RPMI8226: an In Vitro Study - Zonghong Li; Xuewei Yin; Chunyi Lyu; Jingyi Wang; Kui Liu; Siyuan Cui; Shumin Ding; Yingying Wang; Jinxin Wang; Dadong Guo; Ruirong Xu (Biological Trace Element Research, 2024)

Genome-wide identification and functional analysis of the cellulose synthase-like gene superfamily in common oat (Avena sativa L.) - Shanshan Zhang; Haibin Hu; Shumin Cui; Lin Yan; Bing Wu; Shanjun Wei (Phytochemistry, 2024)

Diversity, community structure, and quantity of eukaryotic phytoplankton revealed using 18S rRNA and plastid 16S rRNA genes and pigment markers: a case study of the Pearl River Estuary - Shumin Xu; Guihao Li; Cui He; Yi Huang; Dan Yu; Huiwen Deng; Zhuyin Tong; Yichong Wang; Christine Dupuy; Bangqin Huang; Zhuo Shen; Jie Xu; et al. (Marine Life Science & Technology, 2023)
Understanding consistencies and discrepancies in characterizing diversity and quantity of phytoplankton is essential for better modeling ecosystem change. In this study, eukaryotic phytoplankton in the Pearl River Estuary, South China Sea were investigated using nuclear 18S rRNA and plastid 16S or 23S rRNA genes and pigment analysis. It was found that 18S abundance poorly explained the variations in total chlorophyll a (Chl- a ). However, the ratios of log-transformed 18S abundance to Chl- a in the major phytoplankton groups were generally environment dependent, suggesting that the ratio has potential as an indicator of the physiological state of phytoplankton. The richness of 18S-based operational taxonomic units was positively correlated with the richness of 16S-based amplicon sequence variants of the whole phytoplankton community, but insignificant or weak for individual phytoplankton groups. Overall, the 18S based, rather than the 16S based, community structure had a greater similarity to pigment-based estimations. Relative to the pigment data, the proportion of haptophytes in the 18S dataset, and diatoms and cryptophytes in the 16S dataset, were underestimated. This study highlights that 18S metabarcoding tends to reflect biomass-based community organization of eukaryotic phytoplankton. Because there were lower copy numbers of plastid 16S than 18S per genome, metabarcoding of 16S probably approximates cell abundance-based community organization. Changes in biomass organization of the pigment-based community were sensitive to environmental changes. Taken together, multiple methodologies are recommended to be applied to more accurately profile the diversity and community composition of phytoplankton in natural ecosystems.

Effects of ultrasound–assisted freezing on the quality of large yellow croaker (Pseudosciaena crocea) subjected to multiple freeze–thaw cycles - Hongyue Li; Lei Wang; Jinxiang Wang; Xuepeng Li; Jianrong Li; Fangchao Cui; Shumin Yi; Yongxia Xu; Wenhui Zhu; Hongbo Mi (Food Chemistry, 2023)

A deep learning approach to predict sea surface temperature based on multiple modes - Shuang Xu; Dejun Dai; Xuerong Cui; Xunqiang Yin; Shumin Jiang; Haidong Pan; Guansuo Wang (Ocean Modelling, 2023)

Shifting from homogeneous to heterogeneous surfaces in estimating terrestrial evapotranspiration: Review and perspectives - Yuanbo Liu; Guoyu Qiu; Hongsheng Zhang; Yonghui Yang; Yinsheng Zhang; Quan Wang; Wenzhi Zhao; Li Jia; Xibin Ji; Yujiu Xiong; Chunhua Yan; Ning Ma; et al. (Science China Earth Sciences, 2022)

Targeted drug delivery strategies for the treatment of rheumatoid arthritis - Jinxia Zhang; Ling Jiang; Lihong Sun; Ping Wang; Suhui Sun; Menghong Xu; Lulu Zhang; Shumin Wang; Xiaolong Liang; Ligang Cui (Science China Life Sciences, 2021)

Effects of Selenium on Arsenic-Induced Liver Lesions in Broilers - Zhihua Ren; Huidan Deng; Youtian Deng; Wenjiao Tang; Qiang Wu; Zhicai Zuo; Hengmin Cui; Yanchun Hu; Shumin Yu; Sheng-yu Xu; Junliang Deng (Biological Trace Element Research, 2021)

Insecticide resistance status and detoxification enzymes of wheat aphids Sitobion avenae and Rhopalosiphum padi - Liuping Zhang; Hong Lu; Kun Guo; Shumin Yao; Feng Cui (Science China Life Sciences, 2017)

Simulation of the spatial stresses due to territorial land development on Yellow River Delta Nature Reserve using a GIS-based assessment model - Baolei Zhang; Qiaoyun Zhang; Qingyu Feng; Bohao Cui; Shumin Zhang (Environmental Monitoring and Assessment, 2017)